Psychological Features of 7-8 Grade Students Interaction with Hypertext: A Theoretical and Experimental Study Using an Eye Tracker - Borisenko, N.A.; Ganicheva, A.A.; Mironova, K.V.; Shishkova, S.V. (Psihologičeskaâ nauka i obrazovanie, 2025)
Context and relevance. Currently, hypertext systems are beginning to play an increasingly important role both in the media and in the educational process. Despite a significant array of hypertext studies, most of them are theoretical, and there is a shortage of works on educational hypertext. Objective. To present a pilot experimental study aimed at identifying, using an eye tracker, the features of the primary perception of an educational hypertext by 7-8 grade students, their orientation in the text and the distribution of attention in the process of working with the main text and hyperlinks. Hypotheses: 1) the first reading of the educational hypertext will be sequential, accompanied by students' familiarization with the content of hyperlinks as they appear in the main text; 2) due to the additional cognitive load that occurs when working with hypertext structures, adolescents will have a relatively low level of hypertext comprehension. Methods and materials. Oculographic method, statistical analysis of the oculographic recordings, questionnaire for data collection, authors' diagnostic tool "Hypertext comprehension". The sample included 33 students in grades 7-8 (12 boys and 21 girls, aged 12-15 years (M = 13,8, SD = 0,8)). Results. As for attention, the area of greatest intensity included text passages containing specific factual information. Although, due to the immanent properties of the hypertext, adolescents read it non-linearly, the first reading of the text was relatively consistent, without significant text gaps. High and relatively high levels of comprehension were shown by 12,1% of students, average - 48,5%, low and very low - 39,4%. Conclusions. In the process of reading, teenagers used not the F-pattern, but the commitment pattern. This result is largely explained by the specifics of working with educational hypertext, when students are given the instruction to read analytically. The prevalence of a low level of understanding indicates that schoolchildren have serious problems in semantic reading in general and reading electronic educational hypertexts in particular. Контекст и актуальность. В настоящее время гипертекстовые системы начинают играть все более важную роль и в средствах информации, и в образовательном процессе. Несмотря на значительный массив исследований гипертекста, большинство из них носит теоретический характер, также в дефиците оказываются работы, касающиеся учебного гипертекста. Цель. Выявление с помощью айтрекера психологической специфики взаимодействия учащихся 7-8 классов с учебным гипертекстом, а именно следующих особенностей: 1) первичного восприятия текста и следования установке на последовательное аналитическое чтение, 2) распределения внимания учащихся в процессе работы с основным текстом и содержанием гиперссылок, 3) ориентировки в тексте и его понимания. Гипотезы: 1) первичное чтение учебного гипертекста будет последовательным, сопровождаться ознакомлением учащихся с содержанием гиперссылок по мере их появления в основном тексте; 2) в силу дополнительной когнитивной нагрузки, возникающей при работе с гипертекстовыми структурами, у подростков будет доминировать недостаточно высокий уровень понимания учебного гипертекста. Методы и материалы. Окулографический метод, статистический анализ результатов регистрации окуломоторной активности, анкета с данными испытуемых, авторский диагностический инструментарий «Понимание гипертекста». В выборку вошли 33 учащихся 7-8 классов (12 мальчиков и 21 девочка, возраст - 12-15 лет (M = 13,8, SD = 0,8)). Результаты. С точки зрения внимания в область наибольшей интенсивности попали текстовые отрывки, содержащие конкретную фактуальную информацию. Хотя в силу имманентных свойств, присущих гипертексту, подростки читали текст нелинейно, первичное чтение было относительно последовательным, без существенных текстовых пропусков. Высокий и относительно высокий уровни понимания показали 12,1% испытуемых, средний - 48,5%, низкий и очень низкий - 39,4%. Выводы. В процессе чтения подростки применяли не F-паттерн, а паттерн приверженности, что во многом объясняется спецификой работы с учебным гипертекстом, когда учащимся дается установка на аналитическое чтение. Преобладание низкого уровня понимания свидетельствует о наличии у школьников серьезных проблем в области смыслового чтения в целом и чтения электронного учебного гипертекста в частности.